English workbook Grade 3 supplementary reading material - Barber, Alison; Izabella Hearn; Emma Danihel (Lahore: Oxford university press, 2022)
The series is based on Oxford International Curriculum, PYP and Pakistan Single National Curriculum. Measurable learning objectives allow assessment of students$1 (Bprogress throughout the course. New vocabulary is highlighted leading to pre-reading discussions Texts extracted, read by English speakers, provide pronunciation models and can be found in the Teacher Resource Books. Challenging new words are explained to widen students$1 (Bvocabulary Discussion Time engages students with the unit theme and helps to assess speaking and listening skills Differentiated activities develop students$1 (Bunderstanding of essential skills and provide activities for mixed abilities in one classrooms
Rich international content that delivers reading comprehension, writing, and speaking and listening skills to all students.
Structured teaching frameworks, clear teaching objectives and assessment criteria ensure confident delivery of all the core skills for first and second language learners Comprehensive teaching support enriches teaching, saves planning time, and ensures that language and literacy skills are being taught successfully The series links to Oxford Reading Tree, Project X, and TreeTops reading programmes. Thematic units of engaging fiction and non-fiction expose students to rich language texts from around the world to develop core language and literacy skills.